2014
DOI: 10.1038/nchembio.1522
|View full text |Cite
|
Sign up to set email alerts
|

The voltage-gated sodium channel TPC1 confers endolysosomal excitability

Abstract: The physiological function and molecular regulation of plasma membrane potential have been extensively studied, but how intracellular organelles sense and control membrane potential is not well understood. Using whole-organelle patch clamp recording, we show that endosomes and lysosomes are electrically excitable organelles. In a subpopulation of endolysosomes, a brief electrical stimulus elicits a prolonged membrane potential depolarization spike. The organelles have a previously uncharacterized, depolarizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
213
4
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(228 citation statements)
references
References 47 publications
7
213
4
4
Order By: Relevance
“…The percentage of P2X4-expressing cells with enlarged lysosomes (induced by MA) was decreased from 79.00 Ϯ 2.64 to 30.00 Ϯ 2.66% by TRPML1 co-expression. In contract, co-expression of two-pore channel 2 (TPC2), a Na ϩ release channel (37)(38)(39), and TRPML1-DDKK, a non-conducting TRPML1 mutant (21), did not increase the percentage of cells with enlarged lysosomes induced by MA in P2X4-expressing cells (Fig. 3B), suggesting that lysosome size is specifically controlled by TRPML1.…”
Section: Activation Of Trpml1 Reduces Enlarged Lysosomes Induced By Pmentioning
confidence: 96%
“…The percentage of P2X4-expressing cells with enlarged lysosomes (induced by MA) was decreased from 79.00 Ϯ 2.64 to 30.00 Ϯ 2.66% by TRPML1 co-expression. In contract, co-expression of two-pore channel 2 (TPC2), a Na ϩ release channel (37)(38)(39), and TRPML1-DDKK, a non-conducting TRPML1 mutant (21), did not increase the percentage of cells with enlarged lysosomes induced by MA in P2X4-expressing cells (Fig. 3B), suggesting that lysosome size is specifically controlled by TRPML1.…”
Section: Activation Of Trpml1 Reduces Enlarged Lysosomes Induced By Pmentioning
confidence: 96%
“…15 A decrease in cytoplasmic free Mg 2C is suggested to depolarize the lysosomal membrane potential to affect the transport of all electrogenic coupled and uncoupled transporters, including facilitation of Ca 2C release from the lysosomes. 15 In this line, TPC1 and TPC3 have been probed to be regulated by membrane potential, 11,14,16,63 whereas TPC2 seems to be independent of membrane potential changes, 12,14,72 in spite of the presence of the positively charged voltagesensing motifs in the S4 transmembrane domain. And some studies have reported that acidic luminal pH activates TPCs, 11,14,72 however, in others it was found that acidic pH inhibits TPCs opening.…”
Section: Activity Regulationmentioning
confidence: 99%
“…54 The three types of TPC have positively charged voltage-sensing motifs in the S4 transmembrane domain characteristic of the VGICs superfamily, however, it was suggested that only TPC1 and TPC3 are regulated by voltage, 14,63 whereas TPC2 is not. 8,16 TPC1 mRNA transcripts have a molecular weight around 5 kb and those for TPC2 around 3 kb in murine (Table 1). 1,60 However, northern blot and RT-PCR analysis of TPC1 expression in rats and mice confirmed the presence of 2 TPC1 transcripts with different size, being now referred as TPC1A (the first characterized isoform, » 5 kb) and TPC1B (a smaller isoform, » 4 kb).…”
Section: Structurementioning
confidence: 99%
See 2 more Smart Citations